The Relationship Between the Intensity of Short Video Platform Uses and the Development of Adolescents' Self-Identity——Research on the Mediating Role of Psychological Resilience (Journal of research in medical and health sciences, 2025)
Short video platforms have been deeply integrated into the daily life of adolescents and have become the core tool for their information acquisition and leisure and entertainment, and their use intensity has a profound impact on the development of adolescents' self-identity during the critical period. This study focuses on the relationship between the intensity of short video platform use and adolescents' self-identity and focuses on verifying the mediating role of psychological resilience. The study found that the use of short videos with excessive intensity will impact the clarity and stability of self-identity through social comparison, information overload, and crowding out offline exploration time, which can easily lead to identity diffusion or premature closure. As a positive personal trait, psychological resilience not only plays the role of a "buffer" to alleviate negative effects but also acts as a "conductor" to affect the internal mechanism of action, that is, high-intensity use will consume psychological resources, reduce psychological resilience, and then hinder the formation of healthy self-identity. The research provides directions for families, schools, and society to formulate educational intervention strategies to help adolescents achieve active self-exploration and identity integration in the digital age.
Keywords: Short video platform; Use intensity; Juvenile; Self-identity; Psychological resilience